2010
DOI: 10.1007/s12020-010-9402-9
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide inhibits ghrelin-induced cell proliferation and ERK1/2 activation in GH3 cells

Abstract: Ghrelin stimulates growth hormone release and cell proliferation, which strongly supports a significant role for this peptide in the control of growth hormone-releasing adenomas function and growth. Nitric oxide can influence the stimulatory effects of ghrelin on growth hormone secretion in growth hormone-releasing adenomas. However, the effect of nitric oxide (NO) on ghrelin-induced cell proliferation and the mechanism of this effect in the adenoma were not clarified. In this study, we observed that ghrelin, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 30 publications
1
2
0
Order By: Relevance
“…6f). These studies confirmed in our system the established roles in somatotrope proliferation of GHRHR (through G s ) and of GHSR (through G q/11 and G 12/13 ) 35,36 . For GPR101, the siRNA directed against G αs resulted in an unexpected increase in proliferation, which echoed the finding of increased phospho-ERK activity following G αs depletion described above (Fig.…”
Section: Resultssupporting
confidence: 87%
“…6f). These studies confirmed in our system the established roles in somatotrope proliferation of GHRHR (through G s ) and of GHSR (through G q/11 and G 12/13 ) 35,36 . For GPR101, the siRNA directed against G αs resulted in an unexpected increase in proliferation, which echoed the finding of increased phospho-ERK activity following G αs depletion described above (Fig.…”
Section: Resultssupporting
confidence: 87%
“…However, NO has been shown to act either as a friend or a foe towards cell cycle, in a dual or antagonistic manner as it does for cancer, exerting tumor promoting effects as well as anti‐tumoral effects [Choudhari et al, ]. For example, the NO‐donor s ‐nitroso‐ n ‐acetyl penicillamine (SNAP) has previously been reported to prevent cell cycle progression in many cell types: cerebellar glial cells [Garg et al ], BALB/C 3T3 fibroblasts [Garg and Hassid, ], endothelial cells [Sarkar et al, ], human airway smooth muscle cells [Hamad et al, ], lymphocytes [Kosonen et al, ], chick embryo retina glial cells [Magalhães et al, ], GH3 cells [Tian et al, ] and breast cancer cell lines MDA‐MB‐231 and MCF7 [Laudański et al, ]. By contrast, myoblasts were either stimulated or prevented in their proliferation, emphasizing the duality of NO towards cell proliferation [Ulibarri et al, ].…”
mentioning
confidence: 99%
“…Previous studies have investigated the effect of ghrelin on breast, ovarian and gastric cancer cell lines, although contradictory results were generated (21)(22)(23)). An anti-proliferation effect has been documented in certain studies (24,25), whereas others have described a potential tumor-promoting role of ghrelin (26,27).…”
Section: Discussionmentioning
confidence: 99%